2002
DOI: 10.1124/mol.61.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Dioxin-Inducible Cytochrome P450

Abstract: Representational difference analysis was used to isolate cDNAs corresponding to 2,3,7,8-tetrachlorodibenzo-p-dioxin (dioxin)-inducible genes from mouse Hepa-1 cells. One cDNA encoded a novel cytochrome P450. The human homolog was also isolated and later proved to be human CYP2S1. The induction of mouse CYP2S1 mRNA by dioxin represents a primary response and required the aryl hydrocarbon receptor and aryl hydrocarbon receptor nuclear translocator proteins. The induction of CYP2S1 also occurred in mouse liver an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 11 publications
5
77
0
8
Order By: Relevance
“…Immunoblot analysis clearly demonstrated that our CYP2A13 peptide antibody does not cross-react with CYP2A6 protein (expressed either heterologously or in human liver microsomes) or any of the P450 proteins that are mainly expressed in human liver, that include CYP1A1, CYP1A2, CYP2C9, CYP2C19, CYP2E1, and CYP3A4 (Parkinson, 2001). Moreover, the anti-CYP2A13 antibody does not cross-react with CYP2S1, which is a nonhepatic P450 with high expression in human respiratory tract (Rylander et al, 2001;Rivera et al, 2002;Saarikoski et al, 2005), or mouse CYP2A5, which also shares a high degree of amino acid sequence similarity with both human CYP2A13 and CYP2A6. To our knowledge, this is the first specific antibody that can distinguish CYP2A13 from CYP2A6.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblot analysis clearly demonstrated that our CYP2A13 peptide antibody does not cross-react with CYP2A6 protein (expressed either heterologously or in human liver microsomes) or any of the P450 proteins that are mainly expressed in human liver, that include CYP1A1, CYP1A2, CYP2C9, CYP2C19, CYP2E1, and CYP3A4 (Parkinson, 2001). Moreover, the anti-CYP2A13 antibody does not cross-react with CYP2S1, which is a nonhepatic P450 with high expression in human respiratory tract (Rylander et al, 2001;Rivera et al, 2002;Saarikoski et al, 2005), or mouse CYP2A5, which also shares a high degree of amino acid sequence similarity with both human CYP2A13 and CYP2A6. To our knowledge, this is the first specific antibody that can distinguish CYP2A13 from CYP2A6.…”
Section: Discussionmentioning
confidence: 99%
“…This P450 has only recently been cloned and although assigned to the CYP2 family on the basis of nucleic acid and amino acid sequence homology, it is dioxin inducible (31,32). All other dioxininducible P450s are members of the CYP1 family and this suggests that CYP2S1 may have similar functional characteristics and metabolic substrates as CYP1 P450s (31,32). The immunohistochemical localization of CYP2S1 protein in normal colon is a novel finding although a high level of CYP2S1 mRNA has previously been identified by real-time quantitative PCR in this tissue (33).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 2,3,7,8-tetrachlorodibenzo-p-dioxin, a well characterized Family 1 P450 inducer, induces CYP2S1 (Rivera et al, 2002), and ␣-naphthalene, an active component of coal tar, is oxidized by CYP2S1 (Karlgren et al, 2005). However, there are conflicting reports on the role of CYP2S1 in carcinogen metabolism.…”
Section: Introductionmentioning
confidence: 97%